Stablisation of Expansive Soils by Fly-ash & Wool Waste (International Journal of Innovative Research in Computer Science & Technology, 2022)
In the current study, an effort has been  made to stabilise the local expansionary soils using the  appropriate mix of locally accessible industrial waste with  or without lime. In this study, a sample of high expansive  soils was employed taken from Rajpura (PB) and a sample  of low expansion soils. Industrial waste like fly ash and  wool from local businesses are utilised as additions to  stabilise soil both. Fly ash and wool waste are individually  added to soils with varying quantities (from 5 to 30 percent)  and the weight of a dry soil blend increases by 5 percent.  The geotechnical qualities of solar mixes are examined by a  range of experiments such as CBR, unconfined  compression, triaxial compression and consolidation tests.  After 9 days of water treatment, the uncontained  compression and triaxial compressive tests are performed  on the soil-fly ash and soil-wool waste samples. The  samples of soil-fly ash and soil-wool waste are shown to  reduce the plasticity, swelling and compressibility by  increasing additives and increasing matching CBR, shear  strength and permeability.
Keywords: Stablisation; Eco-friendly; Economical; Waste Reduction